Kenya A Nation Born Again - Deacon, Gregory (2015)
In much of the work on Pentecostalism and development to date, Pentecostals have been considered as individual, adult converts adopting new (in contrast to traditional) socioeconomic approaches. These are seen by some authors as having transformative results for personal wellbeing and economic success as they are no longer subject to the restrictions of state, nation and society; others present opposite conclusions. As an alternative point of departure, this article considers that Charismatic, Pentecostal Christianity has been of great importance in the creation and evolution of Kenya as a state and nation. This understanding is used to illuminate the themes that dominated the country's general election of 2013 and its developmental ramifications. It is suggested that exploring Pentecostalism at the level of nation and state, whilst continuing to allow for the importance of conceptions of personal responsibility, offers an additional and complimentary approach for exploring Pentecostalism and development.
Keywords: Development -- Pentecostal -- Kenya -- Politics -- nationalism